Digitally-assisted analog and RF CMOS circuit design for software-defined radio - Okada, Kenichi; Kousai, Shouhei (Springer, 2011)
This book describes the state-of-the-art in RF, analog, and mixed-signal circuit design for Software Defined Radio (SDR).  It synthesizes for analog/RF circuit designers the most important general design approaches to take advantage of the most recent CMOS technology, which can integrate millions of transistors, as well as several real examples from the most recent research results.  Coverage includes every circuit block for a SDR transceiver, including receiver, transmitter, local oscillator, analog baseband, ADC and DAC,  so that the readers can understand various applications of the digitally-assisted circuit techniques presented. Provides various approaches to realize a transceiver for a SDR using recent CMOS technology, in which fast and millions of transistors are available; Covers entire transceiver circuit blocks, including receiver and transmitter front-ends, local oscillators, analog baseband, ADCs and DACs; Offers analog/RF circuit designers a single-source point of entry to the state-of-the art in RF, analog, and mixed-signal circuit design for Software Defined Radio (SDR).